2008
DOI: 10.1074/jbc.m802539200
|View full text |Cite
|
Sign up to set email alerts
|

The Hairless Phenotype of the Hirosaki Hairless Rat Is Due to the Deletion of an 80-kb Genomic DNA Containing Five Basic Keratin Genes

Abstract: Most models of hereditary hypotrichosis are due to alterations in growth factors and transcription factors, and the examples of causative mutations in hair keratin genes are limited. The Hirosaki hairless rat (HHR) is a mutant strain spontaneously derived from Sprague-Dawley rats (SDRs). In this study, the locus of the responsible gene was examined by linkage analysis and mapped on chromosome 7q36. Because many basic keratin genes are clustered on 7q36, their expression was examined. Reverse transcription-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…A number of previous studies have demonstrated that the production of various chemokines may be regulated by both mitogen-activated protein kinase (MAPK) and nuclear factor kappa-lightchain-enhancer of activated B cells (NF-κB) signaling pathways [13,14]. Activation of the MAPK pathway and NF-κB results in inflammation and chemokine production in airway epithelial cells, mucus hypersecretion, and airway hyperreactvity [15]. Three MAPK subfamilies have been well characterized: ERK, JNK, and p38.…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies have demonstrated that the production of various chemokines may be regulated by both mitogen-activated protein kinase (MAPK) and nuclear factor kappa-lightchain-enhancer of activated B cells (NF-κB) signaling pathways [13,14]. Activation of the MAPK pathway and NF-κB results in inflammation and chemokine production in airway epithelial cells, mucus hypersecretion, and airway hyperreactvity [15]. Three MAPK subfamilies have been well characterized: ERK, JNK, and p38.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in Krt83 have been associated with monilethrix, an autosomal hair disorder that can cause scarring alopecia (Carreras, 1996;van Steensel et al, 2005), and the hairless phenotype of the Hirosaki hairless rat (Nanashima et al, 2008). Hair keratins, and in particular Krt83, have yet to be studied in teeth.…”
Section: Perp and The Regulation Of Gene Expressionmentioning
confidence: 99%
“…In these animals, mutations in the Foxn1 gene are responsible for both the immunodeficiency and the hairless phenotype because Foxn1 is a critical transcription factor for the differentiation and survival of both thymic and skin epithelial cells (14,15). In HHRs, we demonstrated a deletion of 80 kb of genomic DNA containing five basic keratin genes as the reason for the hairless phenotype (16). However, it remains to be determined whether the HHR possesses other genetic abnormalities or exhibits deficiencies in its immune system.…”
Section: Foxp3mentioning
confidence: 92%
“…We have demonstrated the deletion of 80 kb of genomic DNA containing five basic keratin genes in HHRs as the reason for their hairless phenotype (16). The similarity of loci for basic keratin genes and Ly49 genes involves the clustering of genes showing sequence homologies.…”
Section: Figurementioning
confidence: 99%